Comparison of a vertical electric and a vertical magnetic source for cross well CSEM monitoring of CO2 injection - Harris, Brett; Pethick, Andrew (SEG, 2011)
Controlled source electromagnetic transmitters create highly geometric coupled electric and magnetic vector fields that propagate in a way that is dependent on both the orientation of the transmitter and electrical conductivity distribution. There may be a good case for using cross well controlled source electromagnetic methods for monitoring injection of CO2 into deep saline or brackish sandstone reservoirs. The expected range of geo-electrical frameworks that can be used to represent CO2 injection into a saline or brackish sandstone water saturated reservoir is reasonable constrained. That is injection of CO2 would likely create an expanding zone of elevated electrical resistivity that would move out from the injector well into the reservoir. The reservoir would typically be confined above and possibly below by conductive clay or shale dominated sediments. Given this type geo-electrical framework we consider the relative merits of a time harmonic vertical electric and vertical magnetic source for monitoring CO2 injection. We compare numerically generated electric and magnetic fields created in a heterogeneous horizontally layered injection zone with and without injection of CO2. Examples are first provided for a layered earth and then for an expanding 3D volume within permeable layers. We provide images indicating that the vertical electric dipole source is sensitive to CO2 injection into thin resistive sandstone layers in a conductive background.We explore why the more common vertical magnetic dipole source is comparatively insensitive to an increase in resistivity in thin sandstone layers. In summary the vertical magnetic dipole source is a common and practical in-hole source, however in principle the vertical electrical dipole source is likely to be more suitable for monitoring CO2 injection. Certainly the use of a vertical electric dipole source would need to be facilitated within the monitoring well design. Ideally the monitoring interval should be open hole or at least the casing should be slotted, non-metallic and have considerable open area to the formation.